P-081. Oral verruco-papillary lesions in Malaysia - Ghazali, N.; Zain, R.B.; Abdul Rahman, Z.A.; Shanmuhasuntharam, P.; Ghazali, M.N.; Bakri, M.M. (Elsevier, 2001)
Some oral verruco-papillary lesions (VPL) may constitute part of the clinicopathological spectrum of proliferative verrucous leukoplakia (PVL), an aggressive form of leukoplakia. Previous studies in PVL have documented its existence in Western populations but no data exist from the South-East Asia region. Aim: To review the clinicopathological features of persistent, multifocal oral VPL in a Malaysian population. Method: Patients with multiple biopsies of oral VPL were selected from histopathological records. Seven women and three men with diverse ethnic backgrounds were identified. New sections were made and re-examined by a single pathologist. Results: A total of 45 biopsies were reviewed. The mean age at first presentation was 62 years. In 70% of cases, lesions occurred in multiple sites synchronously. The most frequent sites affected were the mandibular gum/vestibule, buccal mucosa and the tongue. Indulgence in risk habits was an over-riding factor in 70% of patients. Surgery was the predominant mode of treatment and recurrences frequently occurred. With hindsight, four cases in this series were diagnosed as PVL. Conclusions: These findings support the existence of PVL as a clinicopathological entity in a Malaysian population. The diagnosis of PVL and institution of early aggressive treatment should be considered when oral VPL are encountered.